Air mass factor sensitivity to a priori profiles in GEMS formaldehyde retrieval during the ASIA-AQ campaign - Gitaek T. Lee; Rokjin J. Park; Hyeong-Ahn Kwon; Jaein I. Jeong; Seungun Lee; Eunjo S. Ha; Yoonbae Chung; Cheol-Hee Kim; Soontae Kim; Chul H. Song; Chang-Keun Song; Jung‐Hun Woo; et al. (Atmospheric Environment, 2026)

Holistic valorization of microalgal slurry into biofuels via integrated simultaneous saccharification and fermentation using co-immobilized tri-enzymes - Geon-Soo Ha; Bikram Basak; Hyun-Jo Ahn; Gahyun Baek; Jae-Hoon Hwang; Hyun-Seog Roh; Woo Jin Chung; Byong-Hun Jeon (Bioresource Technology, 2026)

Lactobacillus Plantarum Q180 Attenuates Hepatic Lipid Accumulation and Regulates Energy Metabolism in High-Fat Diet-Induced Obese Mice - Minseo Cho; Hyunchae Joung; Hyunsoo Jang; Yeon-Woo Kim; Jaeryang Chu; Yoo Jin Kwon; Chang Hun Shin; Jung-Heun Ha; Jisu Lee (Probiotics and Antimicrobial Proteins, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Single-tube total analysis system for ratiometric detection of exosomal miRNAs in breast cancer diagnosis - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Ha Rim Ahn; Young Jo Kim; Jeong-Woo Choi; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2026)

Prevalence and virulence profiles of ESBL-producing Escherichia coli in urinary and blood infections in South Korea - Jong-Hun Ha; Jeong-Ih Shin; Kyu-Min Kim; Jeong-Gyu Choi; Minh Phuong Trinh; Won Jun Anh; Kyung-Min Kang; Hyung-Lyun Kang; Jung-Hyun Byun; Wongwarut Boonyanugomol; Kee Woong Kwon; Myung Hwan Jung; et al. (Folia Microbiologica, 2025)

Hourglass-inspired total analysis system for the sensitive colorimetric detection of exosomal miRNA using the CRISPR-Cas12a system with isothermal amplification - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Jeong-Woo Choi; Ha Rim Ahn; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Dual suppressive effect of p-coumaric acid on pigmentation in B16F10 cells - Sohee Jang; Chang-Woo Ha; Sung-Hyeok Kim; Jung Hun Choi; Seung Namkoong; Sungsil Hong; Hyun Jung Koo; Youn-Kyu Kim; Mediana Hadiwidjaja; Sung Ryul Lee; Eun-Hwa Sohn (Molecular & Cellular Toxicology, 2024)

Photo-crosslinking and layer-by-layer processed organic photodetectors with remarkably suppressed dark current - Min Hun Jee; Byoungwook Park; Ah Young Lee; Seunghyun Rhee; Minyoung Lim; Jung Min Ha; Nayoung Kim; Fujun Zhang; Jong‐Woon Ha; Hyungju Ahn; Jong H. Kim; Mijeong Han; et al. (Chemical Engineering Journal, 2024)

Evaluation of acute, 28-day, 13-week repeated dose oral toxicity and genotoxicity of a herbal extract (HemoHIM G) from Angelica sinensis, Ligusticum chuanxiong, and Peaonia lactiflora - Su-Bin Bak; Hansol Choi; Gyoung-Deuck Kim; Ju Gyeong Kim; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2024)
HemoHIM G is a functional food ingredient composed of a triple herbal combination of Angelica sinensis , Ligusticum chuanxiong , and Paeonia lactiflora , to improve impaired immune function. Considering the pharmacological benefits of its constituent herbal components, HemoHIM G is anticipated to have various health benefits; however, its toxicity has not been thoroughly evaluated. Here, we conducted a comprehensive study to assess the safety of HemoHIM G in terms of acute oral toxicity, 13-week repeat-dose toxicity, and genotoxicity. In the oral acute toxicity study, Sprague–Dawley rats were orally administered a single dose of HemoHIM G at 5000 mg/kg/day, the limit dose for the acute study. No abnormal findings or adverse effects were observed in this study, as confirmed by gross pathology. A 13-week repeated-dose toxicity study was conducted with HemoHIM G at doses of 1250, 2500, and 5000 mg/kg/day to examine the subchronic toxicity in both male and female rats after 28 days of dose-range finding study. No test substance-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology were within normal ranges, further supporting the safety of HemoHIM G. Therefore, the NOAEL of HemoHIM G was considered to be at 5000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronuclei test were conducted to identify the potential genotoxicity of HemoHIM G. HemoHIM G is non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence for the safe use of HemoHIM G as a functional food ingredient.

Recombinant human bone morphogenic protein-2 Induces the Differentiation and Mineralization of Osteoblastic Cells Under Hypoxic Conditions via Activation of Protein Kinase D and p38 Mitogen-Activated Protein Kinase Signaling Pathways - Woo-Hun Ha; Hwa-Sik Seong; Na-Rae Choi; Bong-Soo Park; Yong-Deok Kim (Tissue Engineering and Regenerative Medicine, 2017)

Genomic structure, expression and association study of the porcine FSD2 - Kyu-Sang Lim; Kyung-Tai Lee; Si-Woo Lee; Han-Ha Chai; Gulwon Jang; Ki-Chang Hong; Tae-Hun Kim (Molecular Biology Reports, 2016)

Behavior, PET and histology in novel regimen of MPTP marmoset model of Parkinson’s disease for long-term stem cell therapy - Jun-Won Yun; Jae-Bum Ahn; Euna Kwon; Jae Hun Ahn; Hyung Woo Park; Hwon Heo; Jin-Sung Park; Hyeonjin Kim; Sun Ha Paek; Byeong-Cheol Kang (Tissue Engineering and Regenerative Medicine, 2016)

CoCl2 induces apoptosis through the mitochondria- and death receptor-mediated pathway in the mouse embryonic stem cells - Jin-Ha Lee; Seong-Ho Choi; Min-Woo Baek; Mi-Hwa Kim; Heong-Jun Kim; Sun-Hun Kim; Sang-Jin Oh; Hong-Ju Park; Won-Jae Kim; Ji-Yeon Jung (Molecular and Cellular Biochemistry, 2013)

Identification and characterization of transposable element-mediated chimeric transcripts from porcine Refseq and EST databases - Hong-Seok Ha; Jae-Woo Moon; Jeong-An Gim; Yi-Deun Jung; Kung Ahn; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

In vitro CpG methylation and garcinol reduce PERV LTR promoter activity - Hong-Seok Ha; Young-Choon Lee; Sang-Je Park; Yi-Deun Jung; Kung Ahn; Jae-Woo Moon; Kyudong Han; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)